Green synthesis of silver nanoparticles using Pluchea (Pluchea indica (L.)) leaf extract and antibacterial activity against Staphylococcus aureus and Propionibacterium acnes - Ratnasari, Devi; Kasasiah, Ahsanal; Sulastri, Sulastri; Aida, Fitri (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
Nanotechnology is widely used in the biomedical purpose as a drug delivery system, cancer, and tumor biomarkers. Currently, metals are most used as precursor agents to form nanoparticles such as silver, gold, iron, zinc, and metal oxides. Acne is one of the skin problems caused by the growth of S. aureus and P. acnes bacteria. Treatment of acne using inappropriate antibiotics can lead to resistance. Silver nanoparticles are known to have the ability to kill pathogenic microorganisms. Pluchea leaf extract contains flavonoid, polyphenol, and tannin compounds that can work as natural bioreductors in the formation of silver nanoparticles while inhibiting bacterial growth. This study aims to synthesize silver nanoparticles using Pluchea leaf extract and testing antibacterial activity against Staphylococcus aureus and Propionibacterium acnes. Extraction of Pluchea leaves was carried out using the infusion method with the water solvent. The synthesis of silver nanoparticles was used a shaker incubator at a speed of 150 rpm and a temperature of 37 ºC for 48 hours. Characterization of silver nanoparticles using uv-vis spectrophotometry, particle size analyzer (PSA), zeta potential analyzer, and FESEM-EDX. Antibacterial activity test using microdilution method. The characterization results of silver nanoparticles showed a particle size of 20.50 nm, a zeta potential of -38.6 mV, and a spherical morphological shape. Silver nanoparticles have antibacterial activity against S. aureus and P. acnes with a Minimum Inhibitory Concentration (MIC) value of 62.5 ppm and Minimum Bactericidal Concentration (MBC) value >250 ppm.